SARS-CoV-2 Aiming for the Heart: A Multicenter Italian Perspective About Cardiovascular Issues in COVID-19 - Briguglio, Matteo; Porta, Mauro; Zuffada, Francesca; Bona, Alberto R.; Crespi, Tiziano; Pino, Fabio; Perazzo, Paolo; Mazzocchi, Marco; Giorgino, Riccardo; De Angelis, Giuseppe; Ielasi, Alfonso; De Blasio, Giuseppe; et al. (Frontiers in Physiology, 2020)
The rapid spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the high fatality rate of coronavirus disease 2019 (COVID-19) have been putting a strain on the world since December 2019. Infected individuals exhibit unpredictable symptoms that tend to worsen if age is advanced, a state of malnutrition persists, or if cardiovascular comorbidities are present. Once transmitted, the virus affects the lungs and in predisposed individuals can elicit a sequela of fatal cardiovascular consequences. We aim to present the pathophysiology of COVID-19, emphasizing the major cellular and clinical manifestations from a cardiological perspective. As a roaming viral particle or more likely via the Trojan horse route, SARS-CoV-2 can access different parts of the body. Cardiovascular features of COVID-19 can count myocardial injuries, vasculitis-like syndromes, and atherothrombotic manifestations. Deviations in the normal electrocardiogram pattern could hide pericardial effusion or cardiac inflammation, and dispersed microthrombi can cause ischemic damages, stroke, or even medullary reflex dysfunctions. Tailored treatment for reduced ejection fraction, arrhythmias, coronary syndromes, macrothrombosis and microthrombosis, and autonomic dysfunctions is mandatory. Confidently, evidence-based therapies for this multifaceted nevertheless purely cardiological COVID-19 will emerge after the global assessment of different approaches.